Persepsi Guru tentang Penyelenggaraan Pendidikan Inklusi - Syamsuddin Syamsuddin (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2006)
This explanatory survey aims to investigate teachers' understanding of inclusion program, institutions' readiness in implementing the program success. Questionnaires were distributed to 30 purposively sampled elementary teachers of special educational needs. Interviews were also carried out to validate questionnaire responses. The results of descriptive analyses reveal that teachers had little knowledge about the inclusion program, institutions were not effectively ready to enforce the program, and a number of factors, such as teachers, facilities, and parents, still doubted the program success.